2017
DOI: 10.7150/ijbs.16769
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-135a Regulates Apoptosis Induced by Hydrogen Peroxide in Rat Cardiomyoblast Cells

Abstract: Oxidative stress and apoptosis are the most important pathologic features of ischemic heart disease. Recent research has indicated that microRNAs (miRs) play an essential role in apoptosis. However, whether miRs might regulate B cell lymphoma-2 (Bcl-2) protein in apoptosis during ischemic heart disease is still unclear. The aim of this study, therefore, was to confirm the regulation of microRNA-135a (miR-135a) in oxidative stress injuries induced by hydrogen peroxide (H2O2) in rat cardiomyoblast cells H9c2. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Here we report three miRNAs, miR-135a, miR-451a and miR-486-5p, of which the blood expression levels have been reported to be positively associated with IHD 17 , 20 , 26 , 27 , to be prominently higher (fold change: miR-135a, 1.99; miR-451a, 3.03; miR-486-5p, 2.38) in Austrians than in Japanese. Regarding their pathophysiological significance, miR-135a has been reported to be involved in apoptosis of rat cardiomyoblast cells by down-regulating Bcl-2 35 . miR-486 has been suggested as related to cardiac hypertrophy: miR-486 up-regulation contributes to the activation of Bcl-2-related mitochondrial apoptotic pathways, thereby exhibiting an anti-apoptotic function in cardiomyocytes 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we report three miRNAs, miR-135a, miR-451a and miR-486-5p, of which the blood expression levels have been reported to be positively associated with IHD 17 , 20 , 26 , 27 , to be prominently higher (fold change: miR-135a, 1.99; miR-451a, 3.03; miR-486-5p, 2.38) in Austrians than in Japanese. Regarding their pathophysiological significance, miR-135a has been reported to be involved in apoptosis of rat cardiomyoblast cells by down-regulating Bcl-2 35 . miR-486 has been suggested as related to cardiac hypertrophy: miR-486 up-regulation contributes to the activation of Bcl-2-related mitochondrial apoptotic pathways, thereby exhibiting an anti-apoptotic function in cardiomyocytes 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Among twelve miRNAs, miR-135a, miR-486, miR-2861, and miR-150 are candidate miRNAs explaining the mechanisms for the difference in the incidence of IHD in Austrians and Japanese. miR-135a and miR-486 are involved in apoptosis of cardiomyocytes and cardiac hypertrophy 35 , 36 . miR-2861 regulates osteoblast differentiation and calcification 40 , which may suppress progression of atherosclerotic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that miRNAs are modulated by antioxidant compounds and ROS, however they also can be involved in ROS production. For example miR-135a participates in the regulation of H 2 O 2 -mediated apoptosis in embryonic rat cardiac myoblast cell lines ([ 92 ], Liu, Shi et al, 2017]). A study in an animal model revealed that miR-133a via targeting uncoupling protein 2 (UCP2) participates in inflammatory bowel disease by altering downstream inflammation, oxidative stress and markers of energy metabolism ([ 93 ], Jin, Chen et al, 2017).…”
Section: Cardiac Diseases Related To Myocardial Hypoxia/ischemiamentioning
confidence: 99%
“…Similarly, miR-135a-5p plays a key role on apoptosis in ovarian cancer cells (Tang et al, 2013). Furthermore, miR-135a-5p enhances hydrogen peroxide-induced apoptosis in rat cardiomyoblast (Liu et al, 2017). Additionally, inhibition of miR-135a-5p protects A549 cells from apoptosis (Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Both of these pathways have been found to be triggered in TLE (Henshall, 2007). However, several studies have demonstrated that miR-135a-5p is solely involved in a mitochondria-dependent apoptosis pathway (Wu et al, 2012;Liu et al, 2017;Zhao et al, 2014), which suggests miR-135a-5p could regulate the intrinsic pathway of apoptosis in children with TLE. Although previous studies have shown that miR-135a-5p initiates apoptosis by downregulating expression of pro-apoptotic Bcl-2 family members, including Bcl-2 and Bcl-xL (Zhao et al, 2014;Navarro et al, 2009), a novel target gene of miR-135a-5p was identified in this study and its expressed protein is also an anti-apoptotic protein.…”
Section: Discussionmentioning
confidence: 99%